DEVELOPING ENGLISH PRINTED MATERIAL ON THEME OF OCCUPATION FOR EARLY YOUNG LEARNERS AT PAUD TERPADU JOY KIDS MAKASSAR - Eka Yusmiyati; Kamsinah Kamsinah; Sitti Nurpahmi (Universitas islam Negeri Alauddin Makassar, 2021)
The main objective of this research is to develop English language materials for early young learners. This research was conducted at PAUD Terpadu Joy Kids Makassar. This research developed